Sleep quality of Singapore residents: findings from the 2016 Singapore mental health study - Ying Ying Lee; Jue Hua Lau; Janhavi Ajit Vaingankar; Rajeswari Sambasivam; Saleha Shafie; Boon Yiang Chua; Wai Leng Chow; Edimansyah Abdin; Mythily Subramaniam (Sleep Medicine: X, 2022)
Given the importance of sleep for physical and mental wellbeing, it is crucial to understand the extent of insomnia among community dwellers. However, there is a paucity of population wide epidemiological studies to estimate the prevalence of poor sleep quality. This present study aimed to 1) characterize the sleep quality of a nationally representative sample (n = 6126) of Singapore residents using Pittsburg Sleep Quality Index (PSQI) and 2) identify the sociodemographic correlates of poor sleep in this population. A total of 27.6% of respondents reported poor sleep quality (PSQI score ≥5). Sociodemographic correlates of poor sleep quality in the Singapore population included, but were not limited to, females (AOR = 1.44, 95% CI = 1.17 to 1.77, p-value = 0.001), Malays (vs Chinese) (AOR = 1.53, 95% CI = 1.23 to 1.9, p-value < 0.001), Indians (vs Chinese) (AOR = 1.22, 95% CI = 1.02 to 1.47, p-value = 0.03), ex-smokers (vs non-smokers) (AOR = 1.43, 95% CI = 1.07 to 1.92, p-value = 0.02), persons with comorbid mental health conditions (vs no mental health conditions) (AOR = 14.11, 95% CI = 6.52 to 30.54, p-value < 0.01), and persons with physical multimorbidity (vs no physical conditions) (AOR = 1.63, 95% CI = 1.24 to 2.15, p-value < 0.001). The prevalence of poor sleep in Singapore is comparable to that of other countries in the Asian region. Targeted public health campaigns to psycho-educate vulnerable groups on the importance of good sleep hygiene may improve the overall wellbeing of residents in Singapore.